2018
DOI: 10.7150/thno.23624
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors orchestrate cell growth and differentiation to facilitate liver regeneration

Abstract: Background and Aims: Improving liver regeneration (LR) capacity and thereby liver function reserve is a critical bridging strategy for managing liver failure patients. Since estrogen signaling may participate in LR, our aim was to characterize the roles of ERα and ERβ in LR.Methods: LR capacity and estradiol levels following 2/3rd partial hepatectomy (PHx) were compared in ERα-KO or ERβ-KO vs. wildtype mice. The ERα- or ERβ-related transcriptome and interactome were analyzed from regenerating livers, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 47 publications
1
17
0
1
Order By: Relevance
“…Among these, IFNA5 deletion (5.09% of LGG samples), IFNA8 deletion (5.28% of LGG samples), and DTX3 amplification (3.52% of LGG samples) indicated poor survival in LGG. Kao et al (2018) found that the upregulation of IFNA5 activated the ERβ-Ube3a interaction which further facilitated hepatic progenitor cell differentiation. Human epidemiologic studies showed that SNPs in IFNA8 were significantly associated with the overall survival of patients with WHO grade 2 to 3 gliomas ( Fujita et al, 2010 ).…”
Section: Discussionmentioning
confidence: 96%
“…Among these, IFNA5 deletion (5.09% of LGG samples), IFNA8 deletion (5.28% of LGG samples), and DTX3 amplification (3.52% of LGG samples) indicated poor survival in LGG. Kao et al (2018) found that the upregulation of IFNA5 activated the ERβ-Ube3a interaction which further facilitated hepatic progenitor cell differentiation. Human epidemiologic studies showed that SNPs in IFNA8 were significantly associated with the overall survival of patients with WHO grade 2 to 3 gliomas ( Fujita et al, 2010 ).…”
Section: Discussionmentioning
confidence: 96%
“…These mechanisms include DNA fragmentation (27), TP53 signaling enhancement (28), JNK pathway amplification (29), and cellular differentiation (20,30). Also, Kao et al have shown that ERβ-UBE3A interaction promotes liver cell differentiation while ERα facilitates proliferation (31). However, a previous study showed that without estrogen, MG132 failed to increase basal ERβ-mediated transcription in 293T cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…The ERα-knockout (KO) mice ( ActbCre-ERα loxP/loxP ) and ERβ-KO mice ( ERβ –/– ) used in our study were kindly provided by Prof. Shuyuan Yeh and Prof. Chawnshang Chang, respectively, at the University of Rochester, NY, USA ( 31 , 32 ). To generate ERα-KO mice ( 33 , 34 ), transgenic ERα loxP/loxP mice were crossed with ActbCre (β-actin promoter–driven Cre recombinase) transgenic mice to generate male ERα-KO ( ERα –/– ) mice. The control mice were ERα loxP/loxP without ActbCre .…”
Section: Methodsmentioning
confidence: 99%